Group of women and teenage girls near a large outdoor stone hearth - Unknown:::Creator::::::::::::
Photograph shows a group of women and teenage girls posing for a picture. Several are seated on the right side of a large outdoor stone hearth, and two teenage girls are on the left side of the hearth. They are at the YWCA's Camp Ayun Mapu in Big Basin California.